Functional expression of α(7)-nicotinic acetylcholine receptors by muscle afferent neurons - Baxter, James C. (American Physiological Society, 2014)
The exercise pressor reflex (EPR) is generated by group III and IV muscle afferents during exercise to increase cardiovascular function. Muscle contraction is triggered by ACh, which is metabolized into choline that could serve as a signal of exercise-induced activity. We demonstrate that ACh can induce current in muscle afferents neurons isolated from male Sprague-Dawley rats. The nicotinic ACh receptors (nAChRs) appear to be expressed by some group III-IV neurons since capsaicin (TRPV1) and/or ATP (P(2)X) induced current in 56% of ACh-responsive neurons. α(7)- And α(4)β(2)-nAChRs have been shown to be expressed in sensory neurons. An α(7)-nAChR antibody stained 83% of muscle afferent neurons. Functional expression was demonstrated by using the specific α(7)-nAChR blockers α-conotoxin ImI (IMI) and methyllycaconitine (MLA). MLA inhibited ACh responses in 100% of muscle afferent neurons, whereas IMI inhibited ACh responses in 54% of neurons. Dihydro-β-erythroidine, an α(4)β(2)-nAChR blocker, inhibited ACh responses in 50% of muscle afferent neurons, but recovery from block was not observed. Choline, an α(7)-nAChR agonist, elicited a response in 60% of ACh-responsive neurons. Finally, we demonstrated the expression of α(7)-nAChR by peripherin labeled (group IV) afferent fibers within gastrocnemius muscles. Some of these α(7)-nAChR-positive fibers were also positive for P(2)X(3) receptors. Thus choline could serve as an activator of the EPR by opening α(7)-nAChR expressed by group IV (and possible group III) afferents. nAChRs could become pharmacological targets for suppressing the excessive EPR activation in patients with peripheral vascular disease.